O ensino de língua portuguesa e as concepções de leitura e de linguagem no documento curricular do território maranhense para as séries finais do ensino fundamental - SOUSA, Gabriela Almeida de (2023)
It is known that the teaching and learning of reading are ideologically marked to the extent that the school’s daily activities become structured based on guidelines that are gradually institutionalized by government documents. Having the French Discourse Analysis (DA) as the central theoretical support that supports data analysis, this research object is the effects of meaning constituted by the discourses that mobilize the evocation of the reading and language concepts enunciated in the Maranhão’s Curricular Document (Documento Curricular do Território Maranhense) (DCTMA). In this way, we make use of the fundamental concepts in the field of DA that evidence the linguistic-historical materiality from the studies of Pêcheux ([1965-1975] 2014 and 2012) by proposing a reflection on language having its bases founded on the discomfort of not settle for the evidence and the already-made place, added to the studies of the concepts of Coracini (1995, 2005) and Geraldi (2005) about the classic of reading and language conceptions, as well as the reading concepts of Chartier (2004 ) among other authors who are in line with the theoretical assumptions of French DA. We outlined as the general goal of the research, to investigate how the meanings effects of reading conceptions and language conceptions are constituted in the Portuguese language curriculum organizer for the final grades in elementary school. This research poses as a guiding question: How do the reading and language concepts cross the guidelines of Maranhão’s Curricular Document, constituting implications in the formation of the proficient reader student? Our corpus consisted of excerpts cut from the DCTMA, from which we can see that the institutionalized discourse in face of the prescriptions given in the document, evokes the effect of authority on the teacher's action, (re)affirming the theoretical uniqueness of a reading and language conception to the detriment of other conceptions as a practice mark aimed at meeting the training needs of the labor market. In order to elucidate the functioning of the constituent discursivities of what is stated in the DCTMA guidelines, anchored in the theoretical contribution of discourse analysis, we used the Pechetian theory that proposes that meaning is not simply contained in words, but is produced and negotiated in specific discursive contexts. And that also develops the concept of interdiscourse, referring to the influence of other discourses and ideologies present in the production and interpretation of statements. The analyzes highlight the evidence of the uses and representations of reading (CHARTIER, 2004) as a constituent materiality of the language practices implementation, to reflect on the most diverse forms of reading (BARZOTTO, 1999). We suggest a reinterpretation not of the teacher's work as an effect of blaming him for the failure or mistake, but of the student from Maranhão and the diverse reality in which his school is enrolled, insofar as the teaching and learning of reading transit and means change not of place, but of positioning about the possibilities of reading that reach the student of the final grades of Maranhão’s elementary school.